Viscoelasticity Investigation of Semiconductor NP (CdS and PbS) Controlled Biomimetic Nanoparticle Hydrogels - Zhao, Dan; Zhang, Wang; Chen, Zhi-Zhou (Frontiers in Chemistry, 2022)
The viscoelastic properties of colloidal nanoparticles (NPs) make opportunities to construct novel compounds in many different fields. The interparticle forces of inorganic particles on colloidal NPs are important for forming a mechanically stable particulate network especially the NP-based soft matter in the self-assembly process. Here, by capping with the same surface ligand L-glutathione (GSH), two semiconductor NP (CdS and PbS) controlled biomimetic nanoparticle hydrogels were obtained, namely, CdS@GSH and PbS@GSH. The dependence of viscoelasticity of colloidal suspensions on NP sizes, concentrations, and pH value has been investigated. The results show that viscoelastic properties of CdS@GSH are stronger than those of PbS@GSH because of stronger surface bonding ability of inorganic particles and GSH. The hydrogels formed by the smaller NPs demonstrate the higher stiffness due to the drastic change of GSH configurations. Unlike the CdS@GSH hydrogel system, the changes of NP concentrations and pH value had great influence on the PbS@GSH hydrogel system. The higher the proportion of water in the small particle size PbS@GSH hydrogel system, the greater the mechanical properties. The stronger the alkalinity in the large particle size PbS@GSH hydrogel system, the greater the hardness and storage modulus. Solution˗state nuclear magnetic resonance (NMR) indicated that the ligand GSH forms surface layers with different thickness varying from different coordination modes which are induced by different semiconductor NPs. Moreover, increasing the pH value of the PbS@GSH hydrogel system will dissociate the surface GSH molecules to form Pb2+ and GSH complexes which could enhance the viscoelastic properties.